Generate output for the given logic circuit ↓
Solution ↓
Implement xy + x'y' using baisc gates ↓
Implement x'(y+z) using basic gates ↓
Steps ↓
Implement x'y + y'x using only NAND gate ↓
Implement xy + x'y' using only NAND gate ↓
Implement AB'C + A'BC' using only NAND gate ↓
Implement A + A'B' using only NAND gate ↓
Steps ↓
A' + B'.C' ↓
ab' + a'b ↓
ab + a'b' ↓
The postulates of a mathematical system form the basic assumptions from which is possible to deduce the rules, theoroms, and properties of the system. The most common postulates used to formulate various algebraic structures are:
Postulate 2 x + 0 = x x . 1 = x
---------------------------------------------------------------------------------------------
Postulate 3 x + y = y + x xy = yx
(Commutative)
---------------------------------------------------------------------------------------------
Postulate 4 x.(y + z) = x.y + x.z x + (y.z) = (x + y) . (x + z)
(Distributive)
---------------------------------------------------------------------------------------------
Postulate 5 x + x' = 1 x . x' = 0
_____________________________________________________________________________________________
_____________________________________________________________________________________________
_____________________________________________________________________________________________
_____________________________________________________________________________________________
Theorem 1 x + x = x x . x = x
---------------------------------------------------------------------------------------------
Theorem 2 x + 1 = 1 x . 0 = 0
---------------------------------------------------------------------------------------------
Theorem 3 (x')' = x
(Involution)
---------------------------------------------------------------------------------------------
Theorem 4 x + (y + z) = (x + y) + z x(yz) = (xy)z
(Associative)
---------------------------------------------------------------------------------------------
Theorem 5 (x + y)' = x'y' (xy)' = x' + y'
(De Morgan)
---------------------------------------------------------------------------------------------
Theorem 6 x + xy = x x(x + y) = x
(Absorption)
(i) Prove (x+y) (x+z) = x + yz
LHS = (x+y) (x+z)
= (x.x) + (x.z) + (y.x) + (y.z)
= x + xz + yx + yz [as x.x = x]
= x(1 + z + y) + yz
= x + yz [since 1 + k = 1]
= RHS
(ii) Prove xy + xz + yz' = xz + yz'
LHS = xy + xz + yz'
= xy(z+z') + xz(y+y') + yz'(x+x') [as x+x' = 1]
= xyz + xyz' + xyz + xy'z + xyz' + x'yz'
= xyz + xyz' + xy'z + x'yz' [as xyz + xyz = xyz]
= xyz + xy'z + xyz' + x'yz' [rearranging]
= xz(y+y') + yz'(x+x')
= xz + yz' [as y+y' = 1]
(iii) Simplify F = ABCD + ABCD'
= ABCD + ABCD'
= ABC(D+D')
= ABC [as D+D' = 1]
Example for SOP:
f(a,b) = a'b' + ab'
truth table
a b f
-------------
0 0 1
0 1 0
1 0 1
1 1 0
Another example with 3 variable. ↓
sequence binary minterm designation
representation
-----------------------------------------------------------------
0 000 a'b'c' m0
1 001 a'b'c m1
2 010 a'bc' m2
3 011 a'bc m3
4 100 ab'c' m4
5 101 ab'c m5
6 110 abc' m6
7 111 abc m7
a b c f
--------------
0 0 0 0 m0
0 0 1 1 m1
0 1 0 1 m2
0 1 1 0 m3
1 0 0 1 m4
1 0 1 0 m5
1 1 0 0 m6
1 1 1 0 m7
We know we have to remember where 1 is in the function.
at m1, m2 and m4 we have 1 which is a'b'c + a'bc' + ab'c'
f(a,b,c) = ∑m(1,2,4)
a b c f
--------------
0 0 0 1
0 0 1 1
0 1 0 0
0 1 1 0
1 0 0 1
1 0 1 1
1 1 0 0
1 1 1 1
f(a,b,c) = a'b'c + a'b'c + ab'c' + ab'c + abc
simplifying it
= a'b'(c+c') + ab'(c'+c) + abc
= a'b' + ab' + abc
= b'(a'+a) + abc
= b' + abc
we optimized it so that cost of implementation is less
now b' is available in a'b'c, a'b'c, ab'c', ab'c
f(a,b,c) = a'b + ab'c + c'
convert this to canonical form so that we can identify minterm.
= a'b(c'+c) + ab'c + (a'+a)(b'+b)c'
= a'bc' + a'bc + ab'c + (a'b' + a'b + ab' + ab)c'
= a'bc' + a'bc + ab'c + a'b'c' + a'bc' + ab'c' + abc' (canonical form)
= a'bc' + a'bc + ab'c + a'b'c' + ab'c' + abc' (after uniting common terms)
= ∑m(0, 2, 3, 4, 5, 6)
f(a,b,c) = (a + b') . (a' + b' + c')
(a + b') = (a + b' + c) . (a + b' + c') [not optimized]
sequence binary maxterm designation
representation
-----------------------------------------------------------------
0 000 a+b+c M0
1 001 a+b+c' M1
2 010 a+b'+c M2
3 011 a+b'+c' M3
4 100 a'+b+c M4
5 101 a'+b+c' M5
6 110 a'+b'+c M6
7 111 a'+b'+c' M7
a b c f
-------------
0 0 0 0 M0
0 0 1 0 M1
0 1 0 1 M2
0 1 1 1 M3
1 0 0 0 M4
1 0 1 1 M5
1 1 0 1 M6
1 1 1 0 M7
we have to remember where 0 is occuring
= (a+b+c) . (a+b+c') . (a'+b+c) . (a'+b'+c')
= πM(0,1,4,7)
Converting non-canonical form to canonical form
1. (a) . (a' + b) . (a' + b' + c')
= (a + b'.b + c'.c) . (a' + b + c'.c) . (a' + b' + c')
= [(a+b').(a+b)+c'.c] . (a' + b + c') + (a' + b + c) . (a' + b' + c')
= (a+b'+c') . (a+b'+c) . (a+b+c') . (a+b+c) . (a'+b+c') . (a'+b+c) . (a'+b'+c')
= πM(0,1,2,3,4,5,7)
F(A, B, C, D) = ∑m(1, 3, 7, 11, 15) + ∑d(0, 2, 5)